UJI AKTIVITAS ANTIHIPERGLIKEMIK EKSTRAK ETANOL DAUN SENGKUBAK (Pycnarrhena cauliflora (Miers.) Diels) PADA MENCIT PUTIH JANTAN YANG DIINDUKSI ALOKSAN - Billi, Joseph; Sanggel, Mariyo Jane; Pasaribu, Ezra (Jurnal Borneo Cendekia, 2024)
Diabetes mellitus is a metabolic disorder characterized by increased blood sugar levels or hyperglycemia. The sengkubak plant (Pycnarrhena cauliflora (Miers.) Diels) which contains flavonoids, terpenoids, tannins, and saponins. This study to determine the antihyperglycemic activity of the ethanol extract of sengkubak leaves and to obtain the effective dose of the ethanolic extract of sengkubak leaves on alloxan-induced male white mice. The study used 30 male white mice (Mus musculus L.) which were divided into 6 groups normal control, negative control (CMC-Na 0.5%), and positive control (glibenclamide 0.65 mg/Kg BW), and the three test groups were given ethanol extract of mangosteen leaves with various doses of 200, 400, 800 mg/KgBW. All groups were induced with alloxan monohydrate at a dose of 70mg/KgBW in mice intraperitoneally. Sengkubak leaf extract was macerated using 96% ethanol. The parameters measured included blood sugar levels. The treatment was given for 21 days. The data obtained were analyzed using the One Way ANOVA. The results obtained are sengkubak leaf extract has antihyperglycemic activity in alloxan-induced male white mice. Sengkubak leaf extract at a dose of 800 mg/KgBW showed an effective dose in lowering blood sugar levels.